Long-Term Outcomes and Prognostic Analysis of Computed Tomography-Guided Radioactive 125I Seed Implantation for Locally Recurrent Rectal Cancer After External Beam Radiotherapy or Surgery - Wang, Hao; Wang, Lu; Jiang, Yuliang; Ji, Zhe; Guo, Fuxin; Jiang, Ping; Li, Xuemin; Chen, Yi; Sun, Haitao; Fan, Jinghong; Du, Gang; Wang, Junjie (Frontiers in Oncology, 2021)
Background Management of locally recurrent rectal cancer (LRRC) after surgery or external beam radiotherapy (EBRT) remains a clinical challenge, given the limited treatment options and unsatisfactory outcomes. This study aimed to assess long-term outcomes of computed tomography (CT)-guided radioactive 125I seed implantation in patients with LRRC and associated prognostic factors. Methods A total of 101 patients with LRRC treated with CT-guided 125I seed implantation from October 2003 to April 2019 were retrospectively studied. Treatment procedures involved preoperative planning design, 125I seed implantation, and postoperative dose evaluation. We evaluated the therapeutic efficacy, adverse effects, local control (LC) time, and overall survival (OS) time. Results All the patients had previously undergone surgery or EBRT. The median age of patients was 59 (range, 31–81) years old. The median follow-up time was 20.5 (range, 0.89–125.8) months. The median LC and OS time were 10 (95% confidence interval (CI): 8.5–11.5) and 20.8 (95% CI: 18.7–22.9) months, respectively. The 1-, 2-, and 5-year LC rates were 44.2%, 20.7%, and 18.4%, respectively. The 1-, 2-, and 5-year OS rates were 73%, 31.4%, and 5%, respectively. Univariate analysis of LC suggested that when short-time tumor response achieved partial response (PR) or complete response (CR), or D90>129 Gy, or GTV≤50 cm3, the LC significantly prolonged (P=0.044, 0.041, and <0.001, respectively). The multivariate analysis of LC indicated that the short-time tumor response was an independent factor influencing LC time (P<0.001). Besides, 8.9% (9/101) of the patients had adverse effects (≥grade 3): radiation-induced skin reaction (4/101), radiation-induced urinary reaction (1/101), fistula (2/101), and intestinal obstruction (2/101). The cumulative irradiation dose and the activity of a single seed were significantly correlated with adverse effects ≥grade 3 (P=0.047 and 0.035, respectively). Conclusion CT-guided 125I seed implantation is a safe and effective salvage treatment for LRRC patients who previously underwent EBRT or surgery. D90 and GTV significantly influenced prognosis of such patients.